Rheumatoid Arthritis Therapy Reappraisal Strategies, Opportunities and Challenges - Müller, Rüdiger (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Rheumatoid Arthritis (RA) is a chronic inflammatory disease leading to joint inflammation and destruction. Treatment of RA includes the use of conventional (cs), biologic (b) disease-modifying anti-rheumatic drugs (DMARDs), and oral or intraarticular (IA) glucocorticoids (GCs). All different classes of drugs have shown to halt disease progression in clinical studies. In real life, a physician has more options than just adding or switching to a new ts/bDMARD if any kind of DMARDs has failed. They can modify or optimize the therapy with concomitant csDMARDs, and oral or IA-GC can be added to the treatment regimen. The EULAR states that therapeutic adjustment including the "optimization of csDMARDs dose or route of administration or intra-articular injections of GCs" is recommended. Thus, a new therapeutic agent can be embedded in a whole strategy with parallel optimization of the csDMARD and GC treatment. The idea of treating to target (T2T) for the treatment of RA patients has been around since the late 1990s. Many clinical studies (Ticora, BsSt, Camera) have demonstrated the superiority of a T2T approach. When I talk to physicians, I understand that most of them only rarely inject joints with GC. Therefore, I would like to create an issue on the T2T approach in reality including primary data, reviews, and real-life data demonstrating the general opinion and execution of T2T in treating RA.